EDUKASI MANAJERIAL BERBASIS BALANCED SCORECARD SEBAGAI STRATEGI PENGUATAN KINERJA UMKM BATIK ARANG DI KOTA SAWAHLUNTO - Dorris Yadewani; Nini Nini; Henny Wati; Lina Tio; Novi Hendri; Marshal Imar Pratama; Hendrik Permana; Okma Permata (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The main problems faced include limited managerial knowledge, the lack of integrated strategic planning, and the absence of comprehensive performance measurement tools. This community service activity aims to provide managerial education based on the Balanced Scorecard as a strategy to strengthen the performance of MS Charcoal Batik SMEs. The methods used in this service include socialization, training, mentoring, and evaluation of Balanced Scorecard implementation tailored to the characteristics of SMEs. The results of the activity show an increased understanding among SME actors of managing business performance in a more structured way through the perspectives of finance, customers, internal business processes, as well as learning and growth. It is expected that Balanced Scorecard education can help MS Charcoal Batik SMEs in developing more focused and sustainable business strategies.